Phenotypic and molecular genetic profiles of fluconazole and voriconazole sensitive versus resistant candida spp - Madhavan, Priya (2014)
Frequent use of azole group of antifungal drugs for prophylaxis and treatment of Candida infections has contributed to the emergence of resistant strains, especially among non-albicans Candida species. The present study was done to identify genetic variations and changes in cellular morphology among non-albicans Candida isolates resistant to fluconazole and voriconazole. Candida isolates obtained from two local hospitals were identified using CHROMagar CandidaTM and commercial biochemical test kits. Among these 41 isolates, the most predominant species was C. alis (n=10), followed by C. albicans (n=7), C. parapsilosis (n=6), C. krusei (n=6), C. rugosa (n=6), C. dubliniensis (n=3) and C. glabrata (n=3). Resistance breakpoints of fluconazole and voriconazole were determined for these 41 Candida isolates using the E-test method. C. glabrata and C. parapsilosis strains that were susceptible and resistant towards the two azoles were selected for further studies as they were commonly isolated pathogens in patients with candidiasis in various parts of the world. A less commonly studied species, C. rugosa was also selected. The variations of genes in the resistant and susceptible strains of Candida species wereinvestigated using Random Amplification of Polymorphic DNA-PCR (RAPD-PCR). The isolates were genotyped and grouped into 3 major groups according to their species using composite DNA type (based on three primers) comprising C. glabrata,C. parapsilosis and C. rugosa. Although some of the strains within the same group were highly similar, they were not clones, as indicated by variations in their genotypic profiles. The morphological differences between the drug-resistant and drug-susceptible strains treated with fluconazole and voriconazole were observed with scanning and transmission electron microscopy. A scoring system developed in this study revealed pronounced damage on the cell membrane for cells treated with 10X MIC of fluconazole and MIC of voriconazole. Biofilm formation was studied in these three species, followed by the effect of fluconazole and voriconazole on the pre-formed biofilms using the XTT metabolic assay. The biofilm cells exhibited etween 2 and 64 folds higher MIC50 and MIC80 for both the azoles compared to the planktonic cells. Coating the wells with the azole drugs reduced the MIC of the biofilms for all clinical strains. Expression of candidate genes was compared between the drug-resistant and drug-susceptible strains using semi-quantitative reverse transcription-PCR method in C. glabrata. Candidate genes selected were based on their involvement in ergosterol biosynthesis (ERG11), efflux of drugs (CDR1) and biofilm formation (EPA1, EPA6 and EPA7). The expression level of the selected genes of the Candida isolates was normalized to beta actin gene of Candida and was reported as a ratio. Upregulations were observed in all genes except for EPA7 gene in the resistant strain compared to the ATCC strain. In the susceptible strain, upregulations were observed only in EPA7 and CDR1 genes treated with fluconazole, and in all except EPA7 gene in the voriconazole treated cells. The results obtained in this research contribute to the knowledge on the morphological and genetic characteristics of clinical strains of C. glabrata, C. parapsilosis and C.rugosa sensitive and resistant to fluconazole and voriconazole.